2021
DOI: 10.3389/fvets.2021.751699
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biosecurity in the Control of Campylobacter: A Qualitative Study of the Attitudes and Perceptions of UK Broiler Farm Workers

Abstract: Campylobacter is the leading cause of human bacterial diarrhoeal disease worldwide, with poultry meat products contributing to a large proportion of cases. Due to the ubiquitous presence of Campylobacter in the poultry farm environment, biosecurity is the main area for intervention to prevent colonisation of commercial broiler chicken flocks. However, research has repeatedly demonstrated that farmers' uptake of biosecurity recommendations is often poor. This study explored farmers' attitudes towards biosecurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Recent studies have identified social and psychological factors that influence farmers' decisions about the implementation of biosecurity such as available information ( 9 ), farmers' knowledge and experience ( 10 13 ), social pressure ( 12 , 14 16 ) and time or economic constraints ( 13 , 16 19 ). This array of factors determines what kind of biosecurity measures farmers will adopt.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified social and psychological factors that influence farmers' decisions about the implementation of biosecurity such as available information ( 9 ), farmers' knowledge and experience ( 10 13 ), social pressure ( 12 , 14 16 ) and time or economic constraints ( 13 , 16 19 ). This array of factors determines what kind of biosecurity measures farmers will adopt.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter transmission can also be attributed to human activity on poultry farms; contaminated clothes, skin, and boots of farmworkers and transport crates, either due to biosecurity breaches during the process of partial flock depopulation (thinning) or insufficient implementation of strict biosecurity measures, may contribute to the transmission of Campylobacter from the external environment into poultry houses [ 20 , 33 , 41 ]. Partial flock depopulation is a common practice in many European countries where a portion of a flock is removed and sent for slaughtering before the final slaughter age.…”
Section: Pre-harvest Control Measures (On-farm Control)mentioning
confidence: 99%
“…It is widely believed that raising chickens in modern state-of-the-art production systems and full implementation of biosecurity measures would significantly tackle Campylobacter infections. Yet, Campylobacter remains a challenge despite the fact that such measures are being undertaken in European countries, such as the UK, and New Zealand [ 41 , 44 ]. As a result, novel on-farm mitigation strategies and complementary approaches should be applied.…”
Section: Pre-harvest Control Measures (On-farm Control)mentioning
confidence: 99%
“…Siekkinen et al (8) emphasised that on-farm biosecurity is a critical component of disease prevention and control. Recently, studies have applied both quantitative and qualitative approaches to understand farmers' knowledge, attitudes, and underlying drivers related to on-farm biosecurity practises (9)(10)(11)(12)(13)(14)(15)(16)(17). Studies also discovered how social cues, messages of infection risk and message delivery methods affect farmers' compliance with biosecurity (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%